IMPLEMENTASI PROJECT BASED LEARNING DALAM KETERAMPILAN MENULIS CERPEN SASTRA HIJAU SISWA KELAS XI SMA MUHAMMADIYAH 2 SURABAYA - Yuliani, Yuliani; Affandy, Ali Nuke; Hermoyo, R. Panji (Universitas Muhammadiyah Surabaya, 2024)
The implementation of project based learning in the skills of writing green literary short stories for class XI students of SMA Muhammadiyah 2 Surabaya aims to describe the implementation of the project based learning model in learning and the results of green literary short stories for class XI students of SMA Muhammadiyah 2 Surabaya. This study uses a mixed methods type of the embedded design, which is a research method that combines quantitative and qualitative data simultaneously, with one of the data as a support. The population of this study was class XI MIPA SMA Muhammadiyah 2 Surabaya. While the sample is class XI MIPA 3 and XI MIPA 6 as many as 55 students. The sampling technique for this research was purposive sampling. Data collection was carried out using observation techniques and documentation of learning achievement tests. Data were analyzed with descriptive statistics. The results of this study are the implementation of the project based learning model consisting of six steps, that is: a) determining the project to write green literary short stories; b) designing short story completion steps; c) preparation of project implementation schedule; d) short story completion; e) presentation of short stories; and f) evaluation of the process and results of short stories. Green literary short stories by students fulfill the criteria of: a) use of ecological diction; b) feeling hurt over the destroyed earth; c) efforts to free the earth from destruction; d) stories based on love for the earth; and e) resistance to unfair treatment of the earth. Monitoring activities carried out affect the results of student short stories. The more actively students participate in monitoring, the better the green literary short stories produced. Thus, the project based learning model is appropriate to be applied in learning to write green literary short stories in class XI SMA Muhammadiyah 2 Surabaya.